Essential Oil Compositions and Antimicrobial Activities of Thymbra spicata L. var. spicata L., Lavandula X Intermedia Emeric ex Loisel., Satureja macrantha C. A. MEYER and Rosmarinus officinalis L. - Karakaş,Özgür (2022)
Abstract Medicinal and aromatic plants have been widely using in folk medicine as antimicrobial, anti-inflammatory and antinociceptive agents. The aim of this study was to determine essential oil composition and antimicrobial activity of T. spicata, L. X Intermedia, S. macrantha and R. officinalis. Essential oil components of these plants were obtained by water vapor distillation method using Neo-Clevenger apparatus. Essential oil components were determined by gas chromatography-mass spectroscopy (GC-MS). The main components of these plants are carvacrol (74.26 %) and γ-terpinene (10.28%) in T. spicata, 1,8-cineol (32.48%), linalool (24.38%) and camphor (14.73%) in L. X Intermedia, p-cymene (56.70%), carvacrol (10.96 %) in S. macrantha and camphor (18.26 %), α-pinene (15.51%), 1,8-cineole (11.86%) and borneol (10.39%) in R. officinalis were determined. T. spicata and S. macrantha showed strong effects against three microorganisms. L. X Intermedia and R. officinalis showed strong activity against Candida albicans, while they had moderate effects against Staphylococcus aureus, Escherichia coli.